HPTLC DETERMINATION OF FREE PAROXETINE IN HUMAN SERUM - PRATHIKANTAM PUSHPALATHA; RAJENDRA KUMAR SARIN; MOHD IDRIS; MESINENI ANAND RAO; TULSIDAS RAMACHANDRA RAO BAGGI; M.SATISH VARMA (International Journal of Pharma and Bio Sciences, 2014)
A rapid, sensitive and specific high-performance thin-layer chromatographic (HPTLC) method was developed and validated for quantitative determination of free Paroxetine (PAX) in human serum. Densitometric analysis of free PAX was carried at 293nm after simple liquid-liquid extraction. The method uses HPTLC aluminium plates pre-coated with silica gel G 60F254 as stationary phase and acetone: carbon tetrachloride: triethylamine (5:5:0.3,v/v/v) as mobile phase for the separation of free PAX from serum constituents. The calibration curve was linear (r2 = 0.996) in the tested range of 95-240 ng spot–1 with a limit of detection (LOD) 30 ng spot–1and limit of quantification of (LOQ) 95 ng spot–1. Free drug recovery from serum averaged 94.4% to 99.28%. Intra- and inter-day precision (% RSD) values were <1.83% and <5.66%, respectively. Analysis of free PAX from human serum was successfully performed without interference from endogenous materials and some of the other common drugs of abuse. The ability of this method to quantify free PAX with precision, accuracy and sensitivity makes it useful in forensic examination.